Energy Efficient Constrained Shortest Path First-Based Joint Resource Allocation and Route Selection for Multi-Hop CRNs - Chen, Qianbin; Wang, Ling; Gao, Yuanpeng; Chai, Rong; Huang, Xiaoge (China communications, 2017)
Cognitive radio networks （CRNs）are expected to improve spectrum utilizationefficiently by allowing secondary users （SUs）to opportunistically access the licensed spec-trum of primary users （PUs）. In CRNs, sourceand destination SUs may achieve informationinteraction in an ad hoc manner. In the casethat no direct transmission link between theSU transmission pairs is available, multi-hoprelay SUs can be applied to forward infor-mation for the source and destination SUs,resulting in multi-hop CRNs. In this paper, weconsider a multi-hop CRN consisting of multi-ple PUs, SU transmission pairs and relay SUs.Stressing the importance of transmission hopsand the tradeoff between data rate and powerconsumption, we propose an energy efficientconstrained shortest path first （CSPF）-basedjoint resource allocation and route selection algorithm, which consists of two sub-al- gorithms, i.e., CSPF-based route selection sub-algorithm and energy efficient resource allocation sub-algorithm. More specifically, we first apply CSPF-based route selection sub-algorithm to obtain the shortest candidate routes （SCRs） between the SU pair under the transmission constraints. Then, an energy effi- cient resource allocation problem of the SCRs is formulated and solved by applying iterative algorithm and Lagrange dual method. Simu-lation results demonstrate the effectiveness ofthe proposed algorithm.